Thermoplastic resin composition and molded article

By mixing specific resins in biomass polyamides to form a thermoplastic resin composition, the problems of poor coating properties, impact resistance and creaking sound of the polyamide resin are solved, and excellent moldability, durability and creaking sound suppression effects are achieved.

CN119731268APending Publication Date: 2025-03-28大科能宇菱通株式会社
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380060806.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-14
Filing Date
2023-09-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The conventional polyamide resin has poor coating properties and impact resistance during use, and the size changes are large due to water absorption, making it difficult to suppress the occurrence of creaking sound for a long time.

Method used

By mixing rubber-reinforced vinyl-based graft resin, aromatic vinyl-based copolymer resin and acid-modified vinyl-based resin in polyamide from biomass, a thermoplastic resin composition is formed, which optimizes its moldability, chemical resistance and long-term durability, and suppresses squeaking during dynamic contact.

Benefits of technology

The thermoplastic resin composition has good molding properties, impact resistance, chemical resistance and long-term durability, and effectively suppresses the occurrence of creaking sound when it comes to dynamic contact with other materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731268A_ABST
    Figure CN119731268A_ABST
Patent Text Reader

Abstract

A thermoplastic resin composition containing a polyamide (A) in which at least a portion of the raw material is derived from biomass, a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C), and an acid-modified vinyl resin (D), the thermoplastic resin composition being characterized in that: at least one of the raw materials is a thermoplastic resin; a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C), and an acid-modified vinyl resin (D) are contained in a total of 100 parts by mass of the polyamide (A), the rubber-reinforced vinyl graft resin (B), the aromatic vinyl copolymer resin (C), and the acid-modified vinyl resin (D). The present invention is characterized by containing 20-70 parts by mass of a polyamide (A), 5-45 parts by mass of a rubber-reinforced vinyl graft resin (B), 10-75 parts by mass in total of an aromatic vinyl copolymer resin (C) and an acid-modified vinyl resin (D), and 0.1-40 parts by mass of an acid-modified vinyl resin (D).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition comprising a polyamide using a raw material derived from biomass (organic resources derived from organisms such as plants), having good moldability, excellent impact resistance, chemical resistance, and long-term durability, and being able to suppress the occurrence of squeaking (frictional noise) when dynamically contacting with a member made of the same or other materials. The present invention also relates to a molded article of the thermoplastic resin composition. Background Art

[0002] Thermoplastic resin compositions are widely used as molding materials for parts of vehicles, OA (office automation) equipment, home electric appliances, electric / electronic equipment, building materials, and the like.

[0003] Among them, polyamide resin has the characteristics of excellent mechanical strength, chemical resistance, wear resistance, etc., and is therefore used in various applications such as industrial products such as automobiles, electrical / electronic / mechanical parts, and sports and leisure products. However, polyamide resin has the disadvantages of poor paintability and impact resistance. In addition, polyamide resin is easy to absorb water due to its chemical structure, and there is a problem of large dimensional change. Therefore, in order to improve these shortcomings, a large amount of research has been carried out in the past.

[0004] For example, a rubber-modified nylon composition has been proposed in which an ABS resin is blended with a polyamide resin using a carboxylic acid group-containing copolymer obtained by copolymerizing an unsaturated carboxylic acid with styrene and acrylonitrile as a compatibilizer (see Patent Document 1).

[0005] Known polyamide resins can improve the heat resistance, dimensional stability and rigidity of molded products by adding inorganic fillers such as glass fiber and carbon fiber. For example, a thermoplastic resin composition (referring to patent document 2) formed by mixing glass fiber and carbon fiber in a composition comprising polyamide resin and ABS resin is proposed. The thermoplastic resin composition becomes a molding material with excellent impact resistance, dimensional stability, rigidity and heat resistance and good performance balance.

[0006] Among the thermoplastic resin parts used in these fields (referred to as "parts made of thermoplastic resin composition X"), there are parts used in combination with other parts such as thermoplastic resin parts made of the same or different materials as the thermoplastic resin composition X, cured resin parts, or inorganic material parts made of metals or inorganic compounds. For example, the thermoplastic resin parts are arranged in contact with other parts, or these parts are arranged at a predetermined interval (see Patent Documents 3 and 4). In particular, it is known that when thermoplastic resin parts are adjacent to each other (only the two are in contact, or both are in contact with a bonding portion in a part, or both are arranged at a predetermined interval), due to vibration, rotation, torsion, sliding, impact, etc., one or both of them move or deform and dynamically contact, and a squeaking sound (friction sound) occurs. This squeaking sound is said to be a sound caused by the stick-slip phenomenon generated when two objects rub against each other.

[0007] The stick-slip phenomenon is said to be different from the conventionally known phenomenon of sliding between objects.

[0008] like Figure 1 As shown in , the stick-slip phenomenon is understood as a phenomenon in which the friction force changes greatly and periodically. Figure 2 That is, in the case of Figure 2 As shown in the model of (a), when an object M connected by a spring is placed on a driving table moving at a driving speed V, the object M first moves with the table moving at a driving speed V due to the action of static friction. Figure 2 (b) Then, when the force to be restored by the spring is equal to the static friction force, the object M slides in the direction opposite to the driving speed V. At this time, the object M is subjected to dynamic friction, so when the force of the spring is equal to the dynamic friction force Figure 2 (c) The sliding stops. That is, the vehicle is attached to the driving platform and moves again in the same direction as the driving speed V ( Figure 2 (d)).

[0009] This is called the stick-slip phenomenon.

[0010] like Figure 1 As shown in FIG. 1 , when the difference Δμ between the static friction coefficient μs and the friction coefficient μl at the lower end of the sawtooth waveform is large, it is said that squeaking noise is likely to occur.

[0011] The dynamic friction coefficient is an intermediate value between μs and μl. Therefore, even if the absolute value of the static friction coefficient is small, if Δμ is large, squeaking is likely to occur. Squeaking is the main cause of damaging the comfort and quietness of the interior of a car, office, or home. Therefore, there is a strong demand to suppress or reduce the occurrence of squeaking.

[0012] In recent years, various proposals have been made on techniques for suppressing the occurrence of this squeaking noise (friction noise).

[0013] For example, Patent Document 3 discloses a thermoplastic resin composition comprising a rubber-reinforced aromatic vinyl resin (A, B), a crystalline thermoplastic resin (C) and a fibrous or layered filler (D), wherein the melting point measured according to JIS K7121-1987 is between 0 and 100°C and between 170 and 280°C, and the flexural modulus is greater than 3,000 MPa.

[0014] Patent document 4 discloses an automobile interior component, which is composed of a thermoplastic resin composition, wherein the thermoplastic resin composition comprises: (A) 8 to 93% by mass of a styrene resin, which is composed of a rubber-reinforced styrene resin (A1) and / or a styrene (co)polymer (A2) of the vinyl monomer (b), wherein the rubber-reinforced styrene resin (A1) is obtained by mixing an aromatic vinyl in the presence of a rubber polymer (a) composed of a conjugated diene rubber polymer (a-1) and / or an acrylic rubber polymer (a-2). (A) component, (B) component and (C) component 100% by weight.

[0015] When a thermoplastic resin component repeatedly contacts other components, the surface of the thermoplastic resin component is worn, and sometimes a gap is formed between the thermoplastic resin component and other components. In order to suppress this situation, it is known that, for example, a thermoplastic resin composition containing a polyamide resin as the main component further contains an inorganic filler (see Patent Document 5). However, polyamide resins represented by polyamide 6 are easy to absorb moisture and easily cause dimensional changes, so it is difficult to maintain long-term suppression and reduce the occurrence of squeaking noise.

[0016] On the other hand, in recent years, in order to build a recycling-oriented society, the use of biomass to replace fossil fuel raw materials in the field of materials has attracted attention. Biomass is an organic compound obtained by photosynthesis of carbon dioxide and water. Biomass is a raw material for so-called carbon neutrality (the emission and absorption of carbon dioxide in the environment are the same, so the increase of carbon dioxide as a greenhouse gas can be suppressed) by using it to become carbon dioxide and water again. Recently, the practical application of biomass plastics using these biomass as raw materials has developed rapidly. Attempts have also been made to manufacture polyamides as general polymer materials from these biomass raw materials.

[0017] Prior art literature

[0018] Patent Literature

[0019] Patent Document 1: Japanese Patent Publication No. 7-84549

[0020] Patent Document 2: Japanese Patent Application Publication No. 2002-212383

[0021] Patent Document 3: International Publication No. 2014 / 175332

[0022] Patent Document 4: Japanese Patent Application Publication No. 2011-168186

[0023] Patent Document 5: Japanese Patent Application Publication No. 2019-172759 Summary of the invention

[0024] Problems to be solved by the invention

[0025] An object of the present invention is to provide a thermoplastic resin composition comprising a biomass-derived polyamide, which has good moldability, excellent impact resistance, chemical resistance, and long-term durability, and can suppress the occurrence of squeaking (frictional noise) when dynamically contacting with parts made of the same or other materials.

[0026] Means for solving problems

[0027] The inventors have discovered that by mixing a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C) and an acid-modified vinyl resin (D) in a prescribed proportion into a polyamide (A) derived from biomass, good moldability, excellent impact resistance, chemical resistance and long-term durability can be achieved, and the occurrence of the above-mentioned squeaking noise can be significantly reduced.

[0028] The gist of the present invention is as follows.

[0029] [1] A thermoplastic resin composition comprising a polyamide (A) at least part of which is derived from biomass, a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C) and an acid-modified vinyl resin (D), wherein:

[0030] In 100 parts by weight of the total of polyamide (A), rubber-reinforced vinyl graft resin (B), aromatic vinyl copolymer resin (C) and acid-modified vinyl resin (D), 20 to 70 parts by weight of polyamide (A), 5 to 45 parts by weight of rubber-reinforced vinyl graft resin (B), 10 to 75 parts by weight of aromatic vinyl copolymer resin (C) and acid-modified vinyl resin (D) and 0.1 to 40 parts by weight of acid-modified vinyl resin (D) are contained.

[0031] [2] The thermoplastic resin composition according to [1], wherein the rubber-reinforced vinyl-based graft resin (B) comprises a rubber polymer (b) portion and a resin (m) portion comprising a structural unit derived from a vinyl-based monomer grafted to the rubber polymer (b);

[0032] The weight average particle size of the rubber polymer (b) is 0.20 to 0.70 μm.

[0033] [3] The thermoplastic resin composition according to [2], wherein the rubber-reinforced vinyl graft resin (B) comprises an ethylene / α-olefin rubber polymer (b1) having a melting point of 0 to 100°C as measured in accordance with JIS K7121-1987 as the rubber polymer (b).

[0034] [4] A thermoplastic resin composition as described in [3], wherein the rubber-reinforced vinyl graft resin (B) is obtained by polymerizing a vinyl monomer containing an aromatic vinyl compound in the presence of an ethylene / α-olefin rubber polymer (b1) having a melting point of 0 to 100°C as measured in accordance with JIS K7121-1987.

[0035] [5] A molded article comprising the thermoplastic resin composition according to any one of [1] to [4].

[0036] Effects of the Invention

[0037] According to the thermoplastic resin composition of the present invention, it is possible to provide a molded product comprising a biomass-derived polyamide, which has good moldability, excellent impact resistance, chemical resistance, and long-term durability, and in which the occurrence of squeaking (frictional noise) is suppressed when the product is in dynamic contact with a member made of the same or other materials.

[0038] When the thermoplastic resin composition of the present invention further contains a reinforcing vinyl graft resin using a specific ethylene / α-olefin rubber polymer, a molded article can be obtained in which the occurrence of squeaking noise (friction noise) is suppressed for a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a diagram illustrating the stick-slip phenomenon.

[0040] Figure 2 (a), (b), (c), and (d) are model diagrams of the stick-slip phenomenon.

[0041] Figure 3 This is a schematic cross-sectional view showing an example of how components contact each other.

[0042] Figure 4It is a schematic cross-sectional view showing another example of the contact method.

[0043] Figure 5 is a schematic cross-sectional view showing another example of the contact method.

[0044] Figure 6 It is a schematic cross-sectional view showing another example of the contact method.

[0045] Figure 7 is a schematic cross-sectional view showing another example of the contact method.

[0046] Figure 8 is a schematic cross-sectional view showing another example of the contact method.

[0047] Fig. 9 (A), (B), and (C) are schematic diagrams showing another contact method. Fig. 9 (A) is the top view, Fig. 9 (B) is the side view, Fig. 9 (C) is along Fig. 9 (A) Cross-sectional view along line CC.

[0048] Fig.10 It is shown Fig. 9 A schematic perspective view of component 20 is provided.

[0049] Fig.11 (A), (B), and (C) are schematic diagrams showing another contact method. Fig.11 (A) is the top view, Fig.11 (B) is the side view, Fig.11 (C) is along Fig.11 (A) Cross-sectional view along line CC.

[0050] Fig.12 (A), (B), and (C) are schematic diagrams showing another contact method. Fig.12 (A) is the top view, Fig.12 (B) is the side view, Fig.12 (C) is along Fig.12 (A) Cross-sectional view along line CC.

[0051] Fig.13 is Figure 4 A schematic perspective view of components used in another contact method.

[0052] Fig.14 (A), (B), and (C) are schematic diagrams showing another contact method. Fig.14 (A) is the bottom view. Fig.14 (B) is Fig.14 (A) BB line cross-sectional view, Fig.14(C) is Fig.14 (A) CC line cross-sectional view. DETAILED DESCRIPTION

[0053] Embodiments of the thermoplastic resin composition and the molded article of the present invention will be described in detail below.

[0054] In the present specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid. "(Meth)acrylate" means acrylate and / or methacrylate. "(Meth)acryloyl" means acryloyl and / or methacryloyl.

[0055] "(Co)polymer" refers to homopolymers and / or copolymers.

[0056] [Thermoplastic resin composition]

[0057] The thermoplastic resin composition of the present invention comprises a polyamide (A) at least part of which is derived from biomass as a raw material, a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C) and an acid-modified vinyl resin (D). The thermoplastic resin composition is characterized in that, based on 100 parts by mass of the total of the polyamide (A), the rubber-reinforced vinyl graft resin (B), the aromatic vinyl copolymer resin (C) and the acid-modified vinyl resin (D), the composition contains 20 to 70 parts by mass of the polyamide (A), 5 to 45 parts by mass of the rubber-reinforced vinyl graft resin (B), 10 to 75 parts by mass of the aromatic vinyl copolymer resin (C) and the acid-modified vinyl resin (D) in total. , 0.1 to 40 parts by mass of the acid-modified vinyl resin (D).

[0058] Hereinafter, the biomass-derived polyamide (A) may be simply referred to as "polyamide (A)" or "(A) component". The rubber-reinforced vinyl graft resin (B), the aromatic vinyl copolymer resin (C), and the acid-modified vinyl resin (D) may be respectively referred to as "(B) component", "(C) component", and "(D) component".

[0059] The difference between the component (B) of the present invention and the components (C) and (D) is that the component (B) contains a rubber polymer portion, while the components (C) and (D) do not contain a rubber polymer portion.

[0060] The difference between the component (C) and the component (D) is that the component (D) contains an acid-modified group composed of a carboxyl group and / or an acid anhydride group, whereas the component (C) does not contain these acid-modified groups.

[0061] As described later, when the rubber-reinforced vinyl graft resin (B) is produced, a graft copolymer (B-1) is produced, wherein a resin containing a structural unit derived from a vinyl monomer is chemically bonded to a rubber polymer (b), and a resin (B-2) contains a structural unit derived from a vinyl monomer that is not bonded to the rubber polymer (b) but exists in a free state.

[0062] In the present invention, the graft copolymer (B-1) produced here is defined as the rubber-reinforced vinyl graft resin (B) of component (B), and the resin (B-2) produced simultaneously and not grafted to the rubber polymer is defined as component (C) or component (D).

[0063] When the rubber-reinforced vinyl graft resin (B) is produced, only the rubber polymer to which the vinyl monomer is not grafted remains, although in a very small amount. However, since this proportion is very small, it is included in the rubber-reinforced vinyl graft resin (B).

[0064] The component (B) can be distinguished from the component (C) and / or the component (D) by solvent separation using acetone. The reaction product in the production of the rubber-reinforced vinyl-based graft resin (B) is put into acetone and shaken, and then the acetone-insoluble component obtained by solid-liquid separation by centrifugation or the like corresponds to the component (B). The acetone-soluble component corresponds to the component (C) and / or the component (D).

[0065] The components (C) and (D) of the present invention may be used in the production of the thermoplastic resin composition as acetone-soluble components generated when producing the component (B), or components (C) and (D) produced separately from the production of the component (B) may be used, or both may be used.

[0066] <Polyamide (A)>

[0067] Polyamide (A) is a resin having an acid amide bond (-CO-NH-) in the main chain. Polyamide (A) can be produced by a conventionally known method, i.e., polymerization of lactam or amino acid of a ring structure, or polycondensation of dicarboxylic acid and diamine. Therefore, as polyamide (A), homopolyamide, copolyamide, etc. can be used.

[0068] The polyamide (A) used in the present invention, at least part of which is derived from biomass, is, for example, polyamide 11, polyamide 610, polyamide 1010, polyamide 410, polyamide MXD10 resin, polyamide 11·6T copolymer resin, etc., which is a polyamide using a monomer derived from biomass as at least part of the raw material. From the perspective of easily improving the carbon neutralization effect, the impact resistance of the molded product, and the long-term durability, polyamide 11 is particularly preferred as the polyamide (A).

[0069] Polyamide 11 is a polyamide having a structure in which monomers having 11 carbon atoms are bonded via amide bonds. Typically, polyamide 11 is obtained using aminoundecanoic acid or undecane lactam as a monomer. In particular, aminoundecanoic acid is a monomer obtained from castor oil, and is therefore preferred from the perspective of carbon neutralization. The content of these structural units from monomers having 11 carbon atoms is preferably 50 mol% or more of all structural units of polyamide 11, more preferably 80 mol% or more, and can be 100 mol%.

[0070] Polyamide 11 is generally produced by ring-opening polymerization of the above-mentioned undecane lactam. Polyamide 11 obtained by ring-opening polymerization is generally dried after removing lactam monomers with hot water, and then melt-extruded with an extruder.

[0071] Polyamide 610 is a polyamide resin having a structure in which a diamine having 6 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Hexamethylenediamine and sebacic acid are generally used. Sebacic acid is a monomer obtained from castor oil, so it is preferred from the perspective of carbon neutralization. The total content of the structural unit derived from the monomer having 6 carbon atoms and the structural unit derived from the monomer having 10 carbon atoms is preferably 50 mol% or more, more preferably 80 mol% or more, and may also be 100 mol% in all the structural units of polyamide 610.

[0072] Polyamide 1010 is a polyamide resin having a structure in which a diamine having 10 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, 1,10-decanediamine (decamethylenediamine) and sebacic acid are used. Decamethylenediamine and sebacic acid are monomers obtained from castor oil, so they are preferred from the perspective of carbon neutralization. The total content of these structural units from the monomer having 10 carbon atoms and the structural units from the monomer having 10 carbon atoms is preferably 50 mol% or more, more preferably 80 mol% or more, and can also be 100 mol% in all structural units of polyamide 1010.

[0073] Polyamide 410 is a polyamide resin having a structure in which a diamine having 4 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, tetramethylenediamine and sebacic acid are used. Sebacic acid is a monomer obtained from castor oil, so it is preferred from the perspective of carbon neutralization. The total content of the structural units from the monomer having 4 carbon atoms and the structural units from the monomer having 10 carbon atoms is preferably 50 mol% or more, more preferably 80 mol% or more, and can also be 100 mol% in all the structural units of polyamide 410.

[0074] The ends of the polyamide (A) may be capped with carboxylic acids, amines, etc. Examples of carboxylic acids include aliphatic monocarboxylic acids such as caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid. Examples of amines include aliphatic primary amines such as hexylamine, octylamine, decylamine, laurylamine, myristicamine, palmitamine, stearylamine, and behenylamine.

[0075] The plant content of the polyamide (A) determined by ASTM6866 (determination of radioactive carbon 14C content) is preferably 50% or more, particularly preferably 80 to 100%.

[0076] From the viewpoint of easy mixing with the rubber-reinforced vinyl graft resin (B), the aromatic vinyl copolymer resin (C), and the acid-modified vinyl resin (D), the melting point of the polyamide (A) in accordance with JIS K7121-1987 is preferably 160° C. or higher, more preferably 170° C. or higher. The upper limit of the melting point of the polyamide (A) is not particularly limited, but is usually 280° C.

[0077] The thermoplastic resin composition of the present invention may contain only one type of polyamide (A), or may contain two or more types.

[0078] <Rubber-reinforced vinyl-based graft resin (B)>

[0079] The rubber-reinforced vinyl graft resin (B) comprises a rubber polymer (b) portion and a resin (m) portion containing a structural unit derived from a vinyl monomer grafted to the rubber polymer (b), and the rubber polymer (b) and the resin (m) portion are chemically bonded.

[0080] The rubber polymer (b) of the rubber-reinforced vinyl graft resin (B) includes ethylene α-olefin rubber polymer (b1), diene rubber polymer (b2), acrylic rubber polymer (b3), silicone rubber polymer (b4), etc. From the perspective of mechanical properties such as reduced squeaking and impact resistance, plating, and secondary processing properties such as paintability, it is preferred to include ethylene α-olefin rubber polymer (b1) and / or diene rubber polymer (b2), and it is more preferred to include ethylene α-olefin rubber polymer (b1).

[0081] Therefore, the rubber-reinforced vinyl graft resin (B) is preferably a graft resin obtained by polymerizing a vinyl monomer in the presence of an ethylene·α-olefin rubber polymer and / or a diene rubber polymer (b2), particularly an ethylene·α-olefin rubber polymer (b1).

[0082] (Weight Average Particle Size of Rubbery Polymer (b))

[0083] The weight average particle size of the rubber polymer (b) constituting the rubber-reinforced vinyl graft resin (B) is preferably 0.20 to 0.70 μm, more preferably 0.23 to 0.60 μm, and even more preferably 0.25 to 0.50 μm.

[0084] When the weight average particle size of the rubber polymer (b) is greater than or equal to the above lower limit, a thermoplastic resin composition having excellent impact resistance and squeaking (friction noise) suppression effect can be obtained. When the weight average particle size of the rubber polymer (b) is less than or equal to the above upper limit, a thermoplastic resin composition having excellent chemical resistance can be obtained.

[0085] In the present invention, the average particle size of the rubber polymer (b) is a value measured by the following measurement method 1 or measurement method 2.

[0086] <Method 1 for measuring average particle size>

[0087] The weight average particle size and the number average particle size were determined using Microtrac (manufactured by Nikkiso Co., Ltd., "Nanotrac UPA-EX150" dynamic light scattering method) as a measuring device and pure water as a measuring solvent.

[0088] This measurement method is mainly used to measure the average particle size of the rubber polymer (b) in the rubber-reinforced vinyl-based graft resin (B) obtained by emulsion polymerization.

[0089] It is to be noted that the average particle size of the rubber polymer (b) dispersed in the latex was the same as the average particle size of the rubber polymer (b) in the thermoplastic resin composition, as confirmed by image analysis using an electron microscope.

[0090] <Method 2 for measuring average particle size>

[0091] When producing the rubber-reinforced vinyl graft resin (B), in the case of solution polymerization in which the rubber polymer (b) is dissolved in a solvent, the particle size of the rubber polymer (b) in the thermoplastic resin composition is measured by transmission electron microscopic image analysis of the thermoplastic resin composition to determine the weight average particle size (volume average particle size) and number average particle size.

[0092] This method is mainly used to measure the average particle size of the rubber polymer (b) in the rubber-reinforced vinyl-based graft resin (B) obtained by solution polymerization.

[0093] (Ethylene / α-olefin rubber polymer (b1))

[0094] The ethylene / α-olefin-based rubber polymer (b1) is a copolymer containing a structural unit derived from ethylene and a structural unit derived from an α-olefin.

[0095] Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, and 1-eicosene. These α-olefins may be used alone or in combination of two or more. From the perspective of the appearance and impact resistance of the molded article obtained using the thermoplastic resin composition of the present invention, the number of carbon atoms of the α-olefin is preferably 3 to 20, more preferably 3 to 12, and further preferably 3 to 8.

[0096] Regarding the content ratio of the structural units derived from ethylene and the structural units derived from α-olefins constituting the ethylene / α-olefin-based rubber polymer (b1), from the perspective of obtaining a molded product having good moldability, excellent impact resistance, chemical resistance, long-term durability, and suppressing the occurrence of squeaking (friction noise) when dynamically in contact with parts made of the same or other materials, when the total of the two is set to 100 mass%, it is preferred that the structural units derived from ethylene account for 5 to 95 mass% and the structural units derived from α-olefins account for 5 to 95 mass%, more preferably the structural units derived from ethylene account for 50 to 95 mass% and the structural units derived from α-olefins account for 5 to 50 mass%, and even more preferably the structural units derived from ethylene account for 60 to 95 mass% and the structural units derived from α-olefins account for 5 to 40 mass%.

[0097] In the present invention, the preferred ethylene α-olefin rubber polymer (b1) is an ethylene α-olefin copolymer having a melting point in the range of 0 to 100° C. as determined according to JIS K7121-1987, and within this range, it may also have structural units from other monomers. As other monomers, non-conjugated diene compounds such as alkenyl norbornenes, cyclic dienes, and aliphatic dienes can be cited. The structural units from other monomers can be used alone or in combination of two or more. When the total amount of the structural units constituting the ethylene α-olefin rubber polymer (b1) is set to 100% by mass, the upper limit of the content ratio of the structural units from the non-conjugated diene compounds is preferably 10% by mass, more preferably 5% by mass, and further preferably 3% by mass.

[0098] From the perspective of obtaining a molded product with good moldability, excellent impact resistance and chemical resistance, and the ability to suppress squeaking (friction noise) when in dynamic contact with parts made of the same or other materials, the melting point of the ethylene / α-olefin rubber polymer (b1) is more preferably 10 to 90°C, and further preferably 20 to 80°C.

[0099] The melting point of the ethylene α-olefin rubber polymer (b1) existing in the range of 0 to 100°C means that the rubber polymer has crystallinity. It is believed that when the ethylene α-olefin rubber polymer (b1) has a crystalline part, the occurrence of stick-slip phenomenon is suppressed, and the occurrence of squeaking noise caused by contact with parts made of the same or other materials is reduced.

[0100] From the perspective of fully obtaining the effects of the present invention, the ethylene·α-olefin rubber polymer (b1) is preferably an ethylene·α-olefin copolymer composed of structural units derived from ethylene and structural units derived from α-olefins. As the ethylene·α-olefin rubber polymer (b1), ethylene·propylene copolymer, ethylene·1-butene copolymer, ethylene·1-octene copolymer are particularly preferred, and ethylene·propylene copolymer is particularly preferred.

[0101] These ethylene / α-olefin rubber polymers (b1) can be used alone or in combination of two or more.

[0102] (Diene rubber polymer (b2))

[0103] Examples of the diene rubber polymer (b2) include homopolymers such as polybutadiene and polyisoprene; butadiene copolymers such as styrene-butadiene copolymers, styrene-butadiene-styrene copolymers, acrylonitrile-styrene-butadiene copolymers, and acrylonitrile-butadiene copolymers; and isoprene copolymers such as styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, and acrylonitrile-styrene-isoprene copolymers. These may be random copolymers or block copolymers.

[0104] The diene rubber polymer (b2) may be a cross-linked polymer or a non-cross-linked polymer.

[0105] These diene rubber polymers (b2) can be used alone or in combination of two or more.

[0106] (Acrylic rubber polymer (b3))

[0107] The acrylic rubber polymer (b3) is not particularly limited, but is preferably a (co)polymer of a (meth)acrylic acid alkyl ester compound having an alkyl group with 1 to 8 carbon atoms, or a copolymer of the (meth)acrylic acid alkyl ester compound and a vinyl monomer copolymerizable therewith.

[0108] Specific examples of the alkyl acrylate compound having an alkyl group with 1 to 8 carbon atoms used herein include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, pentyl acrylate, hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, and the like.

[0109] Specific examples of the alkyl methacrylate compound include methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, pentyl methacrylate, hexyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, and cyclohexyl methacrylate.

[0110] Among these compounds, n-butyl acrylate and 2-ethylhexyl acrylate are preferred, and n-butyl acrylate is particularly preferred.

[0111] These can be used alone or in combination of two or more.

[0112] These acrylic rubber polymers (b3) can be used alone or in combination of two or more.

[0113] (Silicone rubber polymer (b4))

[0114] The silicone rubber polymer (b4) is not particularly limited, but is preferably a polyorganosiloxane having a vinyl polymerizable functional group. From the viewpoint of color development, a silicone / acrylic composite rubber is preferred.

[0115] As the silicone / acrylic composite rubber, a silicone / acrylic composite rubber composed of a polyorganosiloxane and an alkyl (meth)acrylate polymer is preferred. The silicone / acrylic composite rubber can be produced, for example, by the method described in Japanese Patent Application Laid-Open No. 2016-125006.

[0116] These silicone rubber polymers (b4) can be used alone or in combination of two or more.

[0117] The vinyl monomer forming the resin (m) portion of the rubber-reinforced vinyl graft resin (B) is not particularly limited, and mainly aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylate compounds, maleimide compounds, and vinyl monomers providing structural units having carboxyl groups, vinyl monomers providing acid anhydride groups, and vinyl monomers having other functional groups described later can be used. Among them, aromatic vinyl compounds and vinyl cyanide compounds are preferably included.

[0118] The aromatic vinyl compound is not particularly limited as long as it is a compound having at least one vinyl bond and at least one aromatic ring. Examples of aromatic vinyl compounds include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, β-methylstyrene, ethylstyrene, p-tert-butylstyrene, vinyltoluene, vinylxylene, vinylnaphthalene, etc. Among them, styrene and α-methylstyrene are preferred, and styrene is particularly preferred. These can be used alone or in combination of two or more.

[0119] Examples of the vinyl cyanide compound include acrylonitrile, methacrylonitrile, ethacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, etc. Among them, acrylonitrile is preferred. These may be used alone or in combination of two or more.

[0120] Examples of the (meth)acrylate compound include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, and benzyl (meth)acrylate. These compounds may be used alone or in combination of two or more.

[0121] As the maleimide compound, maleimide, N-methylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-dodecylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-benzylmaleimide, N-naphthylmaleimide, N-cyclohexylmaleimide, etc. can be mentioned. These can be used alone or in combination of two or more.

[0122] In order to introduce a structural unit derived from a maleimide compound into a polymer chain, for example, a method of copolymerizing an unsaturated dicarboxylic acid anhydride with maleic anhydride and then performing imidization can be applied.

[0123] As the vinyl monomer (carboxyl-containing unsaturated compound) providing a structural unit having a carboxyl group, (meth) acrylic acid, ethacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, cinnamic acid, etc. can be cited. Among them, methacrylic acid is preferred. These can be used alone or in combination of two or more.

[0124] Examples of the vinyl monomer (unsaturated acid anhydride) that provides a structural unit having an acid anhydride group include maleic anhydride, itaconic anhydride, citraconic anhydride, etc. These may be used alone or in combination of two or more.

[0125] In addition to the above-mentioned vinyl monomers, a vinyl monomer having at least one functional group selected from the group consisting of a hydroxyl group, an amino group, an epoxy group, and an oxazoline group can also be used.

[0126] For example, as the vinyl monomer having a hydroxyl group (unsaturated compound containing a hydroxyl group), there can be mentioned hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate; (meth)acrylates having a hydroxyl group such as polypropylene glycol mono(meth)acrylate; o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, o-hydroxy-α-methylstyrene, m-hydroxy-α-methylstyrene, Styrene, p-hydroxy-α-methylstyrene, 2-hydroxymethyl-α-methylstyrene, 3-hydroxymethyl-α-methylstyrene, 4-hydroxymethyl-α-methylstyrene, 4-hydroxymethyl-1-vinylnaphthalene, 7-hydroxymethyl-1-vinylnaphthalene, 8-hydroxymethyl-1-vinylnaphthalene, 4-hydroxymethyl-1-isopropenylnaphthalene, 7-hydroxymethyl-1-isopropenylnaphthalene, 8-hydroxymethyl-1-isopropenylnaphthalene, p-vinylbenzyl alcohol, 3-hydroxy-1-propylene, 4-hydroxy-1-butene, cis-4-hydroxy-2-butene, trans-4-hydroxy-2-butene, 3-hydroxy-2-methyl-1-propylene, etc. These can be used alone or in combination of two or more.

[0127] Examples of the vinyl monomer having an amino group (unsaturated compound containing an amino group) include aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminomethyl acrylate, diethylaminomethyl acrylate, 2-dimethylaminoethyl acrylate, aminoethyl methacrylate, propylaminoethyl methacrylate, dimethylaminomethyl methacrylate, diethylaminomethyl methacrylate, 2-dimethylaminoethyl methacrylate, phenylaminoethyl methacrylate, p-aminostyrene, N-vinyldiethylamine, N-acetylvinylamine, acrylamide, methacrylamide, and N-methylacrylamide. These monomers may be used alone or in combination of two or more thereof.

[0128] Examples of vinyl monomers (unsaturated compounds containing epoxy groups) that provide structural units having epoxy groups include glycidyl (meth)acrylate, 3,4-oxycyclohexyl (meth)acrylate, vinyl glycidyl ether, allyl glycidyl ether, methallyl glycidyl ether, etc. These monomers may be used alone or in combination of two or more.

[0129] As the vinyl monomer having an oxazoline group (unsaturated compound containing an oxazoline group), vinyl oxazoline, 4-methyl-2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 2-vinyl-4,4-dimethyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, 2-isopropenyl-4,4-dimethyl-2-oxazoline, etc. can be mentioned. These can be used alone or in combination of two or more.

[0130] As the above-mentioned resin (m) part, the resin (m1) part containing structural units derived from an aromatic vinyl compound and structural units derived from a cyanide vinyl compound, and the resin (m2) part containing structural units derived from an aromatic vinyl compound, structural units derived from a cyanide vinyl compound and structural units derived from a vinyl monomer providing a structural unit having a carboxyl group, that is, structural units derived from a carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride are preferred, and the resin (m1) part containing structural units derived from an aromatic vinyl compound and structural units derived from a cyanide vinyl compound is more preferred.

[0131] When the resin (m) portion is a resin (m1) portion comprising a structural unit derived from an aromatic vinyl compound and a structural unit derived from a vinyl cyanide compound, the lower limit of the ratio of the total amount of the structural unit derived from the aromatic vinyl compound and the structural unit derived from the vinyl cyanide compound in the total 100% by mass of the structural units derived from vinyl monomers forming the resin (m) portion is preferably 50% by mass, more preferably 70% by mass, and even more preferably 90% by mass, from the viewpoint of the appearance and impact resistance of a molded article obtained using the thermoplastic resin composition of the present invention.

[0132] From the viewpoints of appearance, impact resistance and color tone of a molded article obtained using the thermoplastic resin composition of the present invention, the ratio of the content of the structural unit derived from the aromatic vinyl compound and the content of the structural unit derived from the cyanide vinyl compound in the resin (m1) portion is preferably 50 to 95% by mass of the structural unit derived from the aromatic vinyl compound and 5 to 50% by mass of the structural unit derived from the cyanide vinyl compound, more preferably 60 to 85% by mass of the structural unit derived from the aromatic vinyl compound and 15 to 40% by mass of the structural unit derived from the cyanide vinyl compound, and still more preferably 65 to 80% by mass of the structural unit derived from the aromatic vinyl compound and 20 to 35% by mass of the structural unit derived from the cyanide vinyl compound.

[0133] When the resin (m) part is a resin (m2) part further containing a structural unit from a carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride, the content of the structural unit from the carboxyl-containing unsaturated compound and / or the unsaturated acid anhydride is preferably 0.1 to 20% by mass, more preferably 1 to 20% by mass, and further preferably 2 to 8% by mass in the total 100% by mass of the structural unit from the vinyl monomer forming the resin (m2) part. If it is within the above range, a molded product with good moldability, impact resistance, chemical resistance, long-term durability, and good molded appearance can be obtained.

[0134] The content ratio of the structural unit derived from the aromatic vinyl compound and the structural unit derived from the vinyl cyanide compound in the resin (m2) portion is preferably the same as that in the above-mentioned resin (m1) portion.

[0135] Regarding the content ratio of the rubber polymer (b) portion and the resin (m) portion contained in the rubber-reinforced vinyl graft resin (B), from the perspective of obtaining a molded product having good moldability, excellent impact resistance, chemical resistance, and long-term durability, and capable of suppressing the occurrence of squeaking (friction noise) when dynamically contacting with parts made of the same or other materials, when the total of the two is set to 100 mass%, it is preferred that the rubber polymer (b) portion is 20 to 90 mass% and the resin (m) portion is 10 to 80 mass%, more preferably the rubber polymer (b) portion is 25 to 84 mass% and the resin (m) portion is 16 to 75 mass%, and even more preferably the rubber polymer (b) portion is 30 to 77 mass% and the resin (m) portion is 23 to 70 mass%.

[0136] The grafting rate of the rubber-reinforced vinyl graft resin (B) of component (B) is usually 10 to 150%, preferably 15 to 120%, more preferably 20 to 100%, and particularly preferably 30 to 80%. If the grafting rate of component (B) is within the above range, the impact resistance and moldability of the obtained thermoplastic resin composition will become better.

[0137] The graft ratio of the component (B) can be calculated by the following formula (1).

[0138] Grafting rate (mass %) = ((ST) / T) × 100 (1)

[0139] In the above formula (1), S is the mass (g) of the insoluble component obtained by adding 1 g of component (B) or a mixture of component (B) obtained by the above-mentioned graft polymerization production method and component (C) and / or component (D) into 20 mL of acetone, shaking for 2 hours using an shaker at a temperature of 25°C, and then centrifuging for 60 minutes at a temperature of 5°C using a centrifuge (rotation speed: 23,000 rpm) to separate the insoluble component from the soluble component.

[0140] T is the mass (g) of the rubber polymer (b) contained in 1 g of the component (B).

[0141] The mass of the rubber polymer (b) can be obtained by a method of calculating from the polymerization formula and the polymerization conversion rate, or by a method of obtaining by infrared absorption spectroscopy (IR), thermal decomposition gas chromatography, CHN elemental analysis, or the like.

[0142] The grafting rate of component (B) can be adjusted by, for example, appropriately selecting the type and amount of the chain transfer agent used in the graft polymerization when producing component (B), the type and amount of the polymerization initiator used, the method and time of adding the monomer components during polymerization, the polymerization temperature, etc.

[0143] The thermoplastic resin composition of the present invention may contain only one type of rubber-reinforced vinyl graft resin (B), or may contain two or more types of resins having different types, compositions, physical properties, and the like of structural units.

[0144] As the rubber polymer (b) of the rubber-reinforced vinyl graft resin (B), as described above, ethylene·α-olefin rubber polymer (b1), diene rubber polymer (b2), acrylic rubber polymer (b3), silicone rubber polymer (b4), etc. can be used. Therefore, as the rubber-reinforced vinyl graft resin (B), there are graft resins containing ethylene·α-olefin rubber polymer (b1) as the rubber polymer (b), graft resins containing diene rubber polymer (b2) as the rubber polymer (b), graft resins containing acrylic rubber polymer (b3) as the rubber polymer (b), graft resins containing silicone rubber polymer (b4) as the rubber polymer (b), etc., and two or more of these can be used in combination.

[0145] From the perspective of reducing squeaking noise, it is preferred to use a rubber-reinforced vinyl graft resin (B) containing an ethylene·α-olefin rubber polymer (b1) alone as the rubber polymer (b). In order to impart impact resistance, plating properties, paintability, etc., it is preferred to use a rubber-reinforced vinyl graft resin (B) containing an ethylene·α-olefin rubber polymer (b1) as the rubber polymer (b) and a rubber-reinforced vinyl graft resin (B) containing a diene rubber polymer (b2) as the rubber polymer (b) in combination.

[0146] The rubber reinforced vinyl graft resin (B) can be produced, for example, by graft polymerization of a vinyl monomer consisting of an aromatic vinyl compound and other vinyl compounds that can be copolymerized with the aromatic vinyl compound as desired in the presence of a rubber polymer (b) such as an ethylene α-olefin rubber polymer (b1) having a melting point (Tm) of 0 to 100°C. The polymerization method in the production method is not particularly limited as long as the component (B) as a graft copolymer can be obtained, and a known method can be applied. As the polymerization method, emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, or a polymerization method combining them can be used. Among these polymerization methods, known polymerization initiators, chain transfer agents (molecular weight regulators), emulsifiers, etc. can be appropriately used.

[0147] In the above-mentioned production method, a graft copolymer (B-1) formed by grafting (co)polymers of vinyl monomers onto a rubber polymer (b), i.e., the above-mentioned component (B), and a (co)polymer resin (B-2) of vinyl monomers that are not grafted onto the rubber polymer (b), i.e., a mixed product of the above-mentioned component (C) and / or component (D), are usually obtained. Depending on the circumstances, the above-mentioned mixed product sometimes also contains a rubber polymer (b) to which the (co)polymer is not grafted. The thermoplastic resin composition of the present invention contains component (B), component (C) and component (D) as essential components. In other words, it contains both the above-mentioned component (B) and component (C) and component (D) as essential components. Therefore, the mixed product of the above-mentioned component (B) and component (C) and / or component (D) manufactured as described above can be directly used as a raw material for the thermoplastic resin composition of the present invention as component (B), component (C) and / or component (D).

[0148] The graft copolymer (B-1) as the component (B) can be separated from a mixed product of the component (B) and the resin (B-2) as the component (C) and / or the component (D) by solvent separation using acetone. Specifically, the mixed product of the component (B) and the component (C) and / or the component (D) is put into acetone and shaken, and then centrifuged to obtain the component (B) as an acetone-insoluble component and the component (C) and / or the component (D) as an acetone-soluble component.

[0149] Therefore, the raw material of the component (B) in the thermoplastic resin composition of the present invention may be the acetone-insoluble component separated from the mixed product of the above-mentioned component (B) and the component (C) and / or the component (D) by the above-mentioned acetone separation. Similarly, the raw material of the component (C) and / or the component (D) in the thermoplastic resin composition of the present invention may be the acetone-soluble component separated from the mixed product of the above-mentioned component (B) and the above-mentioned component (C) and / or the component (D) by the above-mentioned acetone separation. The above-mentioned component (B), component (C) and component (D) may be a mixture produced by mixing the above-mentioned separated component (B) and component (C) and / or component (D).

[0150] <Aromatic vinyl copolymer resin (C)>

[0151] The aromatic vinyl copolymer resin (C) is a copolymer having a structural unit derived from a vinyl monomer containing at least an aromatic vinyl compound. The aromatic vinyl copolymer resin (C) preferably has the same structural unit composition as the above-mentioned resin (m1) part containing a structural unit derived from an aromatic vinyl compound and a structural unit derived from a cyanide vinyl compound.

[0152] The aromatic vinyl copolymer resin (C) may be a resin generated as the resin (B-2) when manufacturing the component (B), or may be a resin different from the resin (B-2) obtained by copolymerizing a vinyl monomer containing an aromatic vinyl compound without using a rubbery polymer, or may be a resin containing both.

[0153] When using component (C) produced as resin (B-2) when producing component (B) and component (C) produced separately without using a rubbery polymer, their vinyl monomer compositions, physical properties, etc. may be different or the same.

[0154] The intrinsic viscosity (in methyl ethyl ketone, 30°C) of the component (C) in the thermoplastic resin composition of the present invention is usually 0.1 to 1.5 dL / g, preferably 0.15 to 1.2 dL / g, and more preferably 0.15 to 1.0 dL / g. When the intrinsic viscosity is within the above range, the impact resistance and moldability of the thermoplastic resin composition of the present invention are further improved.

[0155] The intrinsic viscosity [η] of the component (C) and the component (D) described below is measured by the following method.

[0156] First, the acetone-soluble fraction of component (C) or component (D), or a mixed product of component (B) and component (C) and / or component (D) is dissolved in methyl ethyl ketone to prepare five materials with different concentrations. The intrinsic viscosity [η] (dL / g) is calculated from the results of measuring the reduced viscosity of each concentration at 30° C. using an Ubbelohde viscometer.

[0157] The thermoplastic resin composition of the present invention may contain only one component (C), or may contain two or more components that are different in the type, composition, physical properties, etc. of structural units.

[0158] <Acid-modified vinyl resin (D)>

[0159] The acid-modified vinyl resin (D) is a copolymer having at least a structural unit derived from a vinyl monomer having an acid-modified group, i.e., a carboxyl group and / or an acid anhydride group. The acid-modified vinyl resin (D) preferably has the same structural unit composition as the above-mentioned resin (m2) part comprising a structural unit derived from an aromatic vinyl compound, a structural unit derived from a cyanide vinyl compound, and a structural unit derived from a carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride.

[0160] The acid-modified vinyl resin (D) may be a resin produced as the resin (B-2) when producing the component (B), or may be a resin different from the resin (B-2) obtained by copolymerizing a vinyl monomer containing an aromatic vinyl compound and a cyanide vinyl compound with a carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride without using a rubbery polymer, or may be a resin containing both.

[0161] When the component (D) produced as the resin (B-2) when producing the component (B) and the component (D) produced separately without using the rubber polymer are used, their vinyl monomer compositions, physical properties, etc. may be different or the same.

[0162] The intrinsic viscosity (in methyl ethyl ketone, 30°C) of the component (D) in the thermoplastic resin composition of the present invention is usually 0.1 to 1.5 dL / g, preferably 0.15 to 1.2 dL / g, and more preferably 0.15 to 1.0 dL / g. When the intrinsic viscosity is within the above range, the impact resistance and moldability of the thermoplastic resin composition of the present invention are further improved.

[0163] The thermoplastic resin composition of the present invention may contain only one component (D), or may contain two or more components that are different in the type, composition, physical properties, etc. of structural units.

[0164] <Content of each ingredient>

[0165] The content of component (A) contained in the thermoplastic resin composition of the present invention is 20 to 70 parts by mass, preferably 25 to 65 parts by mass, more preferably 30 to 60 parts by mass, based on 100 parts by mass of the total of component (A), component (B), component (C) and component (D).

[0166] If the content of component (A) is above the above lower limit, the impact resistance, chemical resistance, and squeaking reduction effect brought about by the inclusion of component (A) are excellent. In addition, the carbon neutralization effect brought about by the inclusion of polyamide (A) derived from biomass can be improved. If the content of component (A) is below the above upper limit, the content of other components (B) to (D) can be ensured, so that long-term durability is excellent.

[0167] The content of component (B) contained in the thermoplastic resin composition of the present invention is 5 to 45 parts by mass, preferably 7 to 40 parts by mass, and more preferably 10 to 35 parts by mass, based on 100 parts by mass of the total of component (A), component (B), component (C), and component (D).

[0168] If the content of component (B) is greater than or equal to the above lower limit, the impact resistance and squeaking noise reduction effects brought about by the inclusion of component (B) are excellent. If the content of component (B) is less than or equal to the above upper limit, the contents of other components (A), (C), and (D) can be ensured, thereby achieving excellent chemical resistance.

[0169] When two or more components (B) are used in combination, for example, when a rubber-reinforced vinyl graft resin (B) comprising an ethylene·α-olefin rubber polymer (b1) as the rubber polymer (b) and a rubber-reinforced vinyl graft resin (B) comprising a diene rubber polymer (b2) as the rubber polymer (b) are used in combination, the content of each in the thermoplastic resin composition of the present invention is preferably 20 parts by weight of the rubber-reinforced vinyl graft resin (B) comprising an ethylene·α-olefin rubber polymer (b1) relative to 100 parts by weight of the total of the components (A), (B), (C) and (D) from the viewpoint of reducing squeaking noise. The amount of the rubber-reinforced vinyl graft resin (B) containing the diene rubber polymer (b2) is 5 to 30 parts by mass, and the amount of the rubber-reinforced vinyl graft resin (B) containing the diene rubber polymer (b2) is 30 to 1 part by mass. It is more preferred that the amount of the rubber-reinforced vinyl graft resin (B) containing the ethylene·α-olefin rubber polymer (b1) is 10 to 30 parts by mass, and the amount of the rubber-reinforced vinyl graft resin (B) containing the diene rubber polymer (b2) is 20 to 1 part by mass. It is further preferred that the amount of the rubber-reinforced vinyl graft resin (B) containing the ethylene·α-olefin rubber polymer (b1) is 10 to 30 parts by mass, and the amount of the rubber-reinforced vinyl graft resin (B) containing the diene rubber polymer (b2) is 10 to 1 part by mass.

[0170] As described above, the weight average particle size of the rubber polymer (b) of the component (B) used in the present invention is preferably 0.20 to 0.70 μm, particularly preferably 0.23 to 0.60 μm, and particularly preferably 0.25 to 0.50 μm.

[0171] Component (B) may contain a rubber-reinforced vinyl graft resin (B) containing a rubber polymer (b) outside the above-mentioned weight average particle size range. However, if the rubber-reinforced vinyl graft resin (B) contains a rubber polymer (b) having a weight average particle size of less than 0.15 μm, the resulting thermoplastic resin composition tends to have poor impact resistance and poor effects on suppressing the occurrence of squeaking (frictional noise).

[0172] Therefore, when the thermoplastic resin composition of the present invention contains a rubber-reinforced vinyl graft resin (B) comprising a rubber polymer (b) having a weight average particle size of less than 0.15 μm, the content thereof is preferably 45 parts by mass or less, particularly preferably 30 parts by mass or less, and particularly preferably 0 to 20 parts by mass, based on 100 parts by mass of the total of component (A), component (B), component (C) and component (D).

[0173] In the present invention, it is preferred that 30% by mass or more, particularly 50% by mass or more, and especially 70 to 100% by mass of the total mass (100% by mass) of component (B) is a rubber-reinforced vinyl graft resin (B) comprising a rubber polymer (b) having a weight average particle size of 0.20 to 0.70 μm.

[0174] The total content of the component (C) and the component (D) contained in the thermoplastic resin composition of the present invention is 20 to 65 parts by mass, preferably 25 to 60 parts by mass, and more preferably 30 to 55 parts by mass, based on 100 parts by mass of the total of the component (A), the component (B), the component (C), and the component (D).

[0175] If the total content of component (C) and component (D) is above the above lower limit, the impact resistance and long-term durability brought by the inclusion of component (C) and component (D) are excellent. If the total content of component (C) and component (D) is below the above upper limit, the content of other components (A) and (B) can be ensured, so that the impact resistance and chemical resistance are excellent.

[0176] The content of component (D) contained in the thermoplastic resin composition of the present invention is 0.1 to 40 parts by mass, preferably 2 to 38 parts by mass, and more preferably 5 to 36 parts by mass, based on 100 parts by mass of the total of component (A), component (B), component (C), and component (D).

[0177] Component (D) is effective in inhibiting the hydrolysis of component (A) and improving the compatibility of component (A) with component (B) and component (C). If the content of component (D) is above the above lower limit, the above effect brought by component (D) is excellent, and a thermoplastic resin composition with excellent impact resistance, long-term durability, and squeaking suppression can be obtained. When the content of component (D) is too much, components (D) react with each other, reducing the moldability and molded appearance of the thermoplastic resin composition. Therefore, the content of component (D) is below the above upper limit.

[0178] From the perspective of impact resistance and long-term durability, the content of component (C) alone is preferably less than 45 parts by mass, particularly less than 40 parts by mass, and even more preferably less than 35 parts by mass, relative to 100 parts by mass of the total of component (A), component (B), component (C), and component (D).

[0179] For the resin (B-2) generated together with the above-mentioned graft copolymer (B-1) in the manufacture of component (B), it is sometimes impossible to judge whether it belongs to component (C) or component (D) according to the type of the vinyl monomer used in the manufacture of component (B). Usually, when the vinyl monomer used in the manufacture of component (B) contains the above-mentioned carboxyl-containing unsaturated compound and / or unsaturated acid anhydride, resin (B-2) can be regarded as component (D). When not containing carboxyl-containing unsaturated compound and / or unsaturated acid anhydride, resin (B-2) is regarded as component (C).

[0180] The content of the rubber polymer (b) contained in the thermoplastic resin composition of the present invention derived from component (B) is preferably 5 to 80 parts by mass, more preferably 10 to 70 parts by mass, further preferably 15 to 65 parts by mass, and particularly preferably 20 to 60 parts by mass, relative to 100 parts by mass of the total of component (B), component (C), and component (D). If the content of the rubber polymer (b) is within the above range, the mechanical strength and squeaking reduction effect of the molded article composed of the thermoplastic resin composition of the present invention can be further improved.

[0181] For the same reason as the content of the rubber-reinforced vinyl-based graft resin (B) containing the rubber polymer (b) having a weight-average particle size of 0.20 to 0.07 μm in the above-mentioned rubber-reinforced vinyl-based graft resin (B), 30% by mass or more, particularly 50% by mass or more, and especially 70 to 100% by mass of the total amount (100% by mass) of the rubber polymer (b) contained in the thermoplastic resin composition of the present invention is preferably a rubber polymer (b) having a weight-average particle size of 0.20 to 0.70 μm.

[0182] In addition, for the same reasons as in the case of containing the rubber-reinforced vinyl graft resin (B) containing the rubber polymer (b) having a weight-average particle size of less than 0.15 μm, the rubber polymer (b) having a weight-average particle size of less than 0.15 μm in the thermoplastic resin composition of the present invention, based on the total amount (100 mass%) of the rubber polymer (b) contained in the thermoplastic resin composition, is preferably 70 mass% or less, particularly preferably 50 mass% or less, and particularly preferably 0 to 30 mass%.

[0183] <Melt Volume Rate (MVR)>

[0184] The melt volume rate (MVR) of the thermoplastic resin composition of the present invention is preferably 10 to 70 cm2 at 240°C and 98 N. 3 / 10 minutes, particularly preferably 15 to 60 cm 3 / 10 minutes, particularly preferably 20 to 50 cm 3When the MVR is greater than or equal to the above lower limit, the moldability is excellent. When the MVR is less than or equal to the above upper limit, the mechanical strength such as impact resistance is excellent.

[0185] The MVR of the thermoplastic resin composition of the present invention is measured by the method described in the section of Examples described later.

[0186] <Plant Degree>

[0187] From the perspective of carbon neutralization, the plant content of the thermoplastic resin composition of the present invention is preferably 20% or more, more preferably 25% or more, and further preferably 30% or more. The upper limit of the plant content of the thermoplastic resin composition of the present invention is not particularly limited, but is generally 70% or less from the perspective of blending the necessary amounts of the (B) component, the (C) component, and the (D) component with respect to the biomass-derived polyamide (A).

[0188] Here, the plant content of the thermoplastic resin composition of the present invention is determined as the mass ratio of the biomass-derived polyamide (A) in the thermoplastic resin composition multiplied by the percentage of the plant content of the biomass-derived polyamide (A).

[0189] <Noise Risk Index>

[0190] The thermoplastic resin composition of the present invention preferably has a noise risk index of 5 or less, more preferably 3 or less, in a test measured by the method described in the examples below using a stick-slip tester "SSP-02" manufactured by ZIEGLER under the conditions of a temperature of 23°C, a humidity of 50% RH, a load of 5N, and a speed of 1 mm / sec. According to the standard of the German Association of the Automotive Industry (VDA203-260), a noise risk index of 3 or less is considered acceptable. This preferred noise risk index can be satisfied by appropriately adjusting the compounding amounts of components (A) to (D), etc.

[0191] <Method for producing thermoplastic resin composition>

[0192] The thermoplastic resin composition of the present invention can be obtained by mixing component (A), component (B), component (C) and component (D) and other components as desired in a desired blending ratio and melt-kneading. As described above, in the case of manufacturing component (B) by graft polymerization, component (C) and / or component (D) are also generated, thereby obtaining a mixture of component (B) and component (C) and / or component (D). The mixture of component (B) and component (C) and / or component (D) can be used directly as a raw material. In addition, component (C) and / or component (D) manufactured separately from component (B) can also be added to the mixture. The physical properties such as copolymerization composition, intrinsic viscosity, etc. of component (C) and / or component (D) generated when manufacturing component (B) and component (C) and / or component (D) manufactured separately from the manufacture of component (B) may be the same or different.

[0193] As other components other than components (A) to (D) that can be blended in the thermoplastic resin composition of the present invention, there can be mentioned nucleating agents, lubricants, heat stabilizers, antioxidants, ultraviolet absorbers, anti-aging agents, plasticizers, antibacterial agents, colorants, fillers, etc. These components can be blended within the range that does not impair the purpose of the present invention.

[0194] As the filler, a fibrous or layered filler is preferably used.

[0195] Examples of the fibrous filler include inorganic fibers such as glass fibers and ceramic whiskers, and organic fibers such as carbon fibers and aramid fibers.

[0196] Examples of the layered filler include flaky and flat fillers, and specific examples include montmorillonite, hectorite, vermiculite, saponite, and glass flakes.

[0197] When the thermoplastic resin composition of the present invention contains a filler, the content of the filler is preferably 5 to 50 parts by mass, more preferably 8 to 35 parts by mass, and particularly preferably 10 to 25 parts by mass relative to 100 parts by mass of the total of component (A), component (B), component (C), and component (D). When the content of the filler is within the above range, the rigidity of the obtained molded article becomes more excellent, which is preferred.

[0198] The thermoplastic resin composition of the present invention may contain other thermoplastic resins other than components (A) to (D) as needed within the range that does not impair the purpose of the present invention. Examples of other thermoplastic resins include polyvinyl chloride, polymethyl methacrylate resins, polycarbonate (PC) resins, polylactic acid resins, polystyrene resins, impact-resistant polystyrene resins, and ASA resins. Polyamide resins that are not derived from biomass may also be mixed. These may be used alone or in combination of two or more.

[0199] When other thermoplastic resins other than components (A) to (D) are blended into the thermoplastic resin composition of the present invention, the content of the other thermoplastic resins other than components (A) to (D) is preferably 50 parts by mass or less in 100 parts by mass of the total of components (A) to (D) and other thermoplastic resins, from the viewpoint of effectively obtaining the effects of the present invention by using components (A) to (D) in a predetermined ratio.

[0200] The thermoplastic resin composition of the present invention can be produced by mixing the components at a predetermined mixing ratio using a tumble mixer, Henschel mixer, etc., and then melt-kneading the components under appropriate conditions using a kneading machine such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, a kneader, a roll, a feeder-ruder, etc. A preferred kneading machine is a twin-screw extruder.

[0201] When kneading the components, the components may be kneaded together or separately in multiple stages. The components may be kneaded using a Banbury mixer, a kneader or the like and then pelletized using an extruder.

[0202] In order to prevent cutting during kneading, the fibrous filler among the fillers is preferably supplied from the middle of the extruder by a side feeder.

[0203] The melt kneading temperature is usually 200 to 300°C, preferably 220 to 280°C.

[0204] [Molding products]

[0205] The molded article obtained by molding the thermoplastic resin composition of the present invention can be used as at least one member of an article including at least two members in contact with each other, thereby suppressing the occurrence of squeaking noise in the article.

[0206] According to the present invention, there is provided an article (hereinafter sometimes referred to as "the article of the present invention") comprising at least two parts in contact with each other, wherein at least one of the parts is a molded article composed of the thermoplastic resin composition of the present invention. In this case, preferably, two or more parts are molded articles composed of the thermoplastic resin composition of the present invention, and particularly preferably, all parts are molded articles composed of the thermoplastic resin composition of the present invention.

[0207] The method for producing the above-mentioned molded article or component from the thermoplastic resin composition of the present invention is not limited in any way. For example, injection molding, injection compression molding, gas-assisted molding, press molding, blow molding, and profile extrusion molding can be cited. In addition, known methods such as film and sheet molding represented by calendering molding and T-die extrusion molding can be cited.

[0208] The thermoplastic resin composition of the present invention is suitable as a molding material for articles in which at least two of the parts of the above-mentioned articles are in constant or intermittent contact, and the contacting parts of the two parts slightly move or collide with each other when external forces such as vibration, torsion, and impact are applied to the articles. The contacting part may be in any of surface contact, line contact, point contact, etc., or may be partially bonded.

[0209] Specifically, we can cite: Figure 3 An article in which one side of the component 10 and one side of the component 20 are bonded to each other in a butt-jointed state; Figures 4 to 8 An article in which a portion of the component 10 is in contact with a recess formed in the component 20 in a fitted state; etc.

[0210] Specific examples of the article in which the components are in contact with each other in a fitted state include the following (1) to (4) and the like.

[0211] (1) Figure 4 As shown, one end of the component 10 is in contact with the complementary recess formed in the component 20 in a precisely fitted state.

[0212] (2) Figure 5 As shown, each end of the component 10 is in contact with the complementary recessed portion of each component 20 formed at the corner of the component 20 in a precisely fitted state.

[0213] (3) Figure 6 As shown, each end of the component 20 is in contact with the complementary recessed portions formed in the two components 10 arranged substantially parallel to each other in a precisely fitted state.

[0214] (4) Figure 7 As shown, a component 20 having an outer side dimension that is the same as the inner side dimension of the component 10 is inserted into the component 10 in a nested manner, and the inner and outer sides of the two are in a state of being exactly fitted and in contact with each other.

[0215] The two parts of the article of the present invention do not need to fit exactly into each other. Figure 8 As shown, the articles may be such that they fit together with a certain degree of gap or margin, and when external forces such as vibration, torsion, and impact are applied to the articles, they repeatedly come into contact and go out of contact with each other.

[0216] As an article having the above-mentioned contact part, the following can be mentioned. Fig. 9 Items as shown in (A) to (C). Fig. 9 In the articles (A) to (C), component 10 is a square component consisting of a rectangular parallelepiped with the bottom surface completely open. Component 20 is a molded product having the same shape as component 10 and having a rectangular opening formed in the center of the upper surface. Fig. 9As shown in (A) to (C), the component 20 can be fitted into the component 10. The outer peripheral surface of the component 20 and the inner peripheral surface of the component 10 are in contact with each other, and when both are subjected to external forces such as vibration, they are only slightly deformed and repeatedly come into contact and out of contact.

[0217] like Fig.10 As shown, the component 20 has protrusions 30 on the opposite outer sides. Fig. 9 As shown in (A) to (C), the component 10 has holes on two opposing sides for receiving the protrusions 30 of the component 20. When the component 10 is fitted to the component 20, the protrusions 30 are snap-fitted into the holes, so that the fitting of the two components is not easily dislocated.

[0218] By molding at least one of the component 10 and the component 20 using the thermoplastic resin composition of the present invention, for example, even along Fig. 9 Even when an external force is applied in the direction of the arrow (C), the occurrence of squeaking noise can be prevented. The direction of the external force is not limited to Fig. 9 (C), even when external force is applied from other directions, when at least one of the parts 10 and 20 is molded using the thermoplastic resin composition of the present invention, the occurrence of squeaking noise can be prevented. Fig. 9 The cross-sectional shape of the protrusion 30 in (A) to (C) and the shape of the hole in the component 10 are changed to a structure in which both components are press-fitted.

[0219] Fig.11 (A) to (C) show that the parts 10 and 20 are bonded to each other except that the inner side and the outer side of the parts 10 and 20 are bonded to each other using adhesive 31 instead of the protrusions 30 and the holes for snap-fitting therewith. Fig. 9 The articles of (A) to (C) are in the same manner. Instead of the adhesive 31, the components 10 and 20 may be welded to each other by laser welding or the like. This method is suitable when the two components are thermoplastic resin molded products. In laser welding, it is particularly preferred to combine a component composed of a transparent thermoplastic resin that transmits laser light and a thermoplastic resin that absorbs laser light. Specific products include instruments such as vehicle speedometers, lighting lamps, and the like.

[0220] In addition to providing holes at opposite positions of the sides of the components 10 and 20, and fastening the two components by bolts and nuts 33 through the two holes, Fig.12 Examples (A) to (C) show Fig. 9 The same applies to the articles of (A) to (C). Instead of bolts and nuts, screws, pins, rivets, bushings, brackets, hinges, nails, etc. may be used to fix the components 10 and 20.

[0221] A device having a component 18 and a frame-shaped component 28, such as Fig.14Articles such as those shown in (A) to (C) can also be suitably molded using the thermoplastic resin composition of the present invention, wherein the component 18 is as follows: Fig.13 As shown in FIG. 1 , a cylindrical shaft 19 protrudes outward in the longitudinal direction from a rectangular plate-shaped main body and both ends, and a member 28 inserts the shaft 19 of the member 18 and supports the member 18 so that the member 18 can rotate around the shaft 19. By molding at least one of the member 18 and the member 28 with the thermoplastic resin composition of the present invention, it is possible to suppress the occurrence of squeaking noise when the member 18 is rotated around the shaft 19 or when an external force such as vibration is applied to the article.

[0222] like Fig.14 As shown in (A) to (C), when the frame-shaped component 28 has two or more openings 29, the article can be suitably used as a device for adjusting the flow rate and direction of air according to the angle of the component 18. Examples of such devices include air outlets of air conditioners, air purifiers, blowers, etc. for home and vehicle use.

[0223] Among the above articles, the occurrence of squeaking noise can be significantly reduced by making at least one of the components 10, 18 and the components 20, 28 into a molded article composed of the thermoplastic resin composition of the present invention. Other articles can also be made into a molded article composed of the thermoplastic resin composition of the present invention.

[0224] Examples of materials constituting the member composed of a material other than the thermoplastic resin composition of the present invention include various thermoplastic resins, thermosetting resins, rubbers, organic materials, inorganic materials, and metal materials.

[0225] Examples of thermoplastic resins constituting the components made of materials other than the thermoplastic resin composition of the present invention include polyvinyl chloride, polyethylene, polypropylene, AS resin, ABS resin, AES resin, ASA resin, polymethyl methacrylate resin, polystyrene resin, high-impact polystyrene resin, ethylene-vinyl acetate (EVA) resin, polyamide (PA) resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polycarbonate (PC) resin, polylactic acid resin, PC / ABS resin, PC / AES resin, PA / ABS resin, PA / AES resin, etc. These may be used alone or in combination of two or more.

[0226] Examples of the thermosetting resin constituting the member made of a material other than the thermoplastic resin composition of the present invention include phenol resins, epoxy resins, urea resins, melamine resins, unsaturated polyester resins, etc. These may be used alone or in combination of two or more.

[0227] Examples of the rubber constituting the member made of a material other than the thermoplastic resin composition of the present invention include chloroprene rubber, polybutadiene rubber, ethylene-propylene rubber, various synthetic rubbers such as SEBS, SBS, and SIS, and natural rubber, etc. These may be used alone or in combination of two or more.

[0228] Examples of organic materials constituting the member composed of materials other than the thermoplastic resin composition of the present invention include insulating boards, MDF (medium density fiberboard), hardboard, particleboard, lumber core (lambda core), LVL (laminated veneer lumber), OSB (oriented board), PSL (parallel strand lumber), WB (wafer particleboard), hard fiberboard, soft fiberboard, raw core plywood, board core plywood, special core plywood, veneer core plywood, laminated sheets and boards of paper impregnated with tapping resin, boards obtained by mixing fine pieces and linear bodies of (waste) paper and the like with an adhesive and heating and compressing them, various woods, etc. These can be used alone or in combination of two or more.

[0229] Examples of inorganic materials constituting the parts composed of materials other than the thermoplastic resin composition of the present invention include calcium silicate boards, flexible boards, homogeneous cement boards, gypsum boards, gypsum lining boards, reinforced gypsum boards, gypsum laths, decorative gypsum boards, composite gypsum boards, various ceramics, glass, etc. These can be used alone or in combination of two or more.

[0230] Examples of the metal material constituting the member made of a material other than the thermoplastic resin composition of the present invention include iron, aluminum, copper, and various alloys, etc. These can be used alone or in combination of two or more.

[0231] Among these, thermoplastic resins, thermosetting resins and rubbers are preferred, and ABS resins, AES resins, PC resins, ABS resins, PC / AES resins and polymethyl methacrylate resins are particularly preferred.

[0232] When at least one of the parts of the article of the present invention is molded from the thermoplastic resin composition of the present invention, the occurrence of squeaking noise can be suppressed even when the parts repeatedly come into contact and out of contact with each other due to vibration, sliding, etc. Therefore, the article of the present invention can be suitably used for automobile parts, office equipment parts, residential parts, home appliance parts, etc.

[0233] When the automobile part is a molded article of the thermoplastic resin composition of the present invention, the occurrence of squeaking noise can be significantly reduced even when the part repeatedly comes into contact and out of contact with other parts due to vibration during vehicle running.

[0234] When the thermoplastic resin composition of the present invention contains a diene rubber, it is excellent in fracture characteristics at low temperatures and is therefore particularly suitable for automobile interior parts.

[0235] Examples of such automotive parts include door trims, door linings, pillar trims, consoles, door pockets, ventilators, ducts, plate-shaped blades of air conditioners, valves, shutters, instrument protection covers, instrument panel upper trims, instrument panel lower trims, A / T indicators, two-position switches (slides, slide plates), switch bezels, grille front deicers, grille side deicers, cover clusters, instrument bottom covers, masks (mask switches, mask radios, etc.), glove boxes, pockets (pocket trims, card pockets, etc.), steering wheel horn gaskets, switch components, exterior parts for guide systems, etc. Among them, the ventilators, plate-shaped blades of air conditioners, valves, shutters, switch components, exterior parts for guide systems, etc. are particularly suitable.

[0236] When office equipment parts are molded articles of the thermoplastic resin composition of the present invention, the occurrence of squeaking noise can be significantly reduced even when the parts repeatedly come into contact and out of contact with other parts due to vibration during operation of the equipment or opening and closing of desk drawers.

[0237] When a housing component is a molded article of the thermoplastic resin composition of the present invention, the occurrence of squeaking noise can be significantly reduced even when the component repeatedly comes into contact and out of contact with other components due to opening and closing of a door or a sliding door.

[0238] When the home appliance parts are molded articles of the thermoplastic resin composition of the present invention, the occurrence of squeaking noise can be greatly reduced even when the parts repeatedly come into contact and out of contact with other parts due to vibration during operation of the equipment. Such home appliance parts include exterior parts such as housings and frames, interior parts, parts around switches, parts of movable parts, and the like.

[0239] The molded article of the present invention not only reduces the occurrence of squeaking noise, but also has a good feel and high rigidity, and is therefore particularly suitable as, for example, parts of electrical or electronic equipment, optical equipment, lighting equipment, office equipment, or home appliances, automobile interior parts, and residential interior parts. Among them, it is particularly suitable as parts of vehicles such as automobiles that are sometimes touched by hand, such as handles such as auxiliary handles, steering wheels, door handles, and portable items.

[0240] Examples of the parts of electric or electronic equipment and optical equipment include housings and covers of cameras such as digital video cameras and still cameras that are often touched by hands; housings and covers of laptop computers, mobile phones, and portable information terminals.

[0241] Examples of lighting equipment components include panels, covers, connectors, and switch peripheral components of ceiling lamps.

[0242] Examples of office equipment parts include exterior parts such as housings and frames, interior parts, parts around switches, parts for movable parts, desk lock parts, desk drawers, and paper trays for copiers.

[0243] Examples of home appliance parts include exterior parts such as casings and housings, interior parts, parts around switches, and parts of movable parts.

[0244] Examples of automobile interior parts include handles such as door handles, steering wheels, and assist handles, as well as door trims, door linings, pillar trims, consoles, console boxes, center panels, door pockets, ventilators, ducts, air conditioners, instrument covers, instrument panel upper trims, instrument panel lower trims, A / T indicators, two-position switches (slides, slide plates), switch bezels, grille front de-icers, grille side de-icers, cover clusters, instrument bottom covers, masks (mask switches, mask radios, etc.), glove boxes, pockets (pocket trims, card pockets, etc.), steering wheel horn gaskets, switch components, and exterior components for guide systems.

[0245] As the parts for residential interior decoration, there are door handles, shelf doors, seat dampers, table folding leg movable parts, door switch dampers, sliding door rails, curtain rails, etc.

[0246] Example

[0247] The present invention will be described in more detail below by way of examples, but the present invention is not limited to the following examples.

[0248] Hereinafter, parts and % are by mass unless otherwise specified.

[0249] [Measurement and evaluation methods]

[0250] The measurement and evaluation methods of various physical properties and characteristics in the following Examples and Comparative Examples are as follows.

[0251] (1) Determination of melt volume rate (MVR)

[0252] The thermoplastic resin composition is measured in accordance with ISO 1133. MVR is a measure of the fluidity, that is, moldability, of the thermoplastic resin composition.

[0253] (2) Evaluation of wet heat aging resistance based on melt volume rate (MVR)

[0254] After the pellets of the thermoplastic resin composition were left to stand for 500 hours in a constant temperature and humidity chamber "PL-2SPH" manufactured by ESPEC under the conditions of 60°C and 80% RH, the pellets were taken out of the constant temperature and humidity chamber and the melt volume rate (MVR) was measured. The change rate of MVR was calculated by the following formula. The smaller the change rate, the better the wet heat aging resistance.

[0255] Change rate of MVR due to damp heat aging (%) = (MVR after damp heat aging / MVR before damp heat aging) × 100

[0256] (3) Evaluation of impact resistance based on V-notch Charpy impact strength

[0257] The thermoplastic resin composition was injection molded using an injection molding machine "IS-170FA" (trade name) manufactured by Toshiba Machine at a barrel temperature of 250°C, an injection pressure of 80 MPa, and a mold temperature of 60°C, and a molded piece with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm was collected. For this test piece, the V-notch Charpy impact strength (kJ / m 2 ).

[0258] (4) Evaluation of hygroscopic impact resistance based on V-notch Charpy impact strength

[0259] After the molded piece for the Charpy test with the V-notch was left to stand for 168 hours in a constant temperature and humidity chamber "PL-2SPH" manufactured by ESPEC at 23°C and 50% RH, the test piece was taken out of the constant temperature and humidity chamber and the Charpy impact strength was measured. The change rate of the Charpy impact strength was calculated by the following formula. The change rate is a standard indicating that the closer it is to 100%, the less likely it is to absorb moisture.

[0260] Change rate of Charpy impact strength due to moisture absorption (%) = (Charpy impact strength after moisture absorption / Charpy impact strength before moisture absorption) × 100

[0261] (5) Evaluation of chemical resistance using sunscreen

[0262] A long strip test piece (150 mm × 10 mm × 2 mm) made by injection molding of a thermoplastic resin composition under the same conditions as in (3) above is fixed along a bending molding test fixture having a surface with a gradually changing curvature. Next, a liquid medicine is applied to the test piece and placed in an environment of 23°C for 48 hours. After the test piece is placed, it is confirmed whether there are scratches and cracks, and the critical strain [%] is calculated from the curvature of the test fixture. As the liquid medicine, a sunscreen ("ANESSA" manufactured by Shiseido) is used.

[0263] The larger the critical strain value, the better the chemical resistance.

[0264] (6) Evaluation of squeak noise after thermal degradation (determination of noise risk index)

[0265] The thermoplastic resin composition was injection molded using an injection molding machine "IS-170FA" (trade name) manufactured by Toshiba Machine under the conditions of a barrel temperature of 250°C, an injection pressure of 50 MPa, and a mold temperature of 60°C to obtain a molded product having a length of 150 mm, a width of 100 mm, and a thickness of 4 mm. A test piece having a length of 60 mm, a width of 100 mm, and a thickness of 4 mm and a test piece having a length of 50 mm, a width of 25 mm, and a thickness of 4 mm were cut out using a circular saw. Next, the ends of the test piece were chamfered using sandpaper #100, and fine burrs were removed using a cutter to obtain two test pieces for evaluation of squeaking noise, one large and one small.

[0266] The above-mentioned evaluation test piece was placed in an oven tank adjusted to 80°C ± 5°C for 300 hours, and then cooled at 25°C for 24 hours to obtain a heat aging evaluation test piece. The two heat-aged test pieces of different sizes were set in a stick-slip tester "SSP-02" manufactured by ZIEGLER, and the noise risk index was measured when rubbed three times with an amplitude of 20 mm under the conditions of temperature 23°C, humidity 50% RH, load 5N, and speed 1mm / sec.

[0267] The greater the noise risk index, the more likely it is to produce squeaking. This test method evaluates the performance by thermal aging, so the sustainability of the squeaking reduction effect can also be evaluated.

[0268] (7) Evaluation of squeaking noise after moisture absorption (noise risk index)

[0269] The squeak evaluation test piece was placed in an oven adjusted to 80°C ± 5°C for 300 hours, cooled at 25°C for 24 hours for heat aging, and the obtained evaluation test piece was further placed in a constant temperature and humidity chamber "PL-2SPH" manufactured by ESPEC at 25°C and 50% RH for 168 hours. The noise risk index of the obtained evaluation test piece was measured in the same manner as above.

[0270] (8) Heat resistance (HDT)

[0271] The deflection temperature was measured by the horizontal method with a load of 1.8 MPa in accordance with ISO 75-2:2013 edition.

[0272] [Raw materials used]

[0273] In the following Examples and Comparative Examples, the raw materials used for producing the thermoplastic resin composition were the following commercially available products or raw materials produced according to the following Production Examples.

[0274] <Polyamide (A)>

[0275] As polyamide (A), the following commercially available products were used.

[0276] PA11: "Rilsan BMNO" manufactured by Arkema (polyamide 11, plant content: 100%, melting point: 190°C)

[0277] PA1010: "Vestamid Terra DS22" manufactured by Daicel-Evonik (polyamide 1010, plant content: 100%, melting point: 200°C)

[0278] PA610: "Rilsan SMVO" manufactured by Arkema (polyamide 610, plant content: 62%, melting point: 225°C)

[0279] <Production Example 1: Production of a mixed product of component (B1) and component (C1)>

[0280] Into a 20-liter stainless steel autoclave equipped with a ribbon-type stirring blade, a continuous additive adding device, a thermometer, etc., 30 parts of an ethylene-propylene copolymer (ethylene / propylene = 78 / 22 (%), Mooney viscosity (ML1+4, 100°C) 20, melting point (Tm): 40°C, glass transition temperature (Tg): -50°C) as an ethylene-α-olefin rubber polymer, 50 parts of styrene, 20 parts of acrylonitrile, 0.5 parts of tert-dodecyl mercaptan, and 110 parts of toluene were added, and the internal temperature was raised to 75°C. The contents of the autoclave were stirred for 1 hour to prepare a uniform solution. Then, 0.45 parts of tert-butyl peroxyisopropyl monocarbonate was added, and the internal temperature was further raised. After reaching 100°C, the polymerization reaction was carried out at a stirring speed of 100 rpm while maintaining the temperature. From the fourth hour after the start of the polymerization reaction, the internal temperature was raised to 120°C, and the reaction was further carried out for 2 hours while maintaining the temperature, and the polymerization reaction was terminated. The polymerization conversion rate was 98%.

[0281] After that, the internal temperature was cooled to 100°C, 0.2 parts of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenol)-propionate and 0.02 parts of dimethyl silicone oil: KF-96-100 cSt (trade name: manufactured by Shin-Etsu Silicone Co., Ltd.) were added, and the reaction mixture was extracted from the autoclave, and the unreacted products and the solvent were distilled off by steam distillation, and then the reaction mixture was heated to 100°C using a 1% ethanol solution. The volatile components were substantially degassed by an extruder (barrel temperature: 220° C., vacuum degree: 760 mmHg) with a vent port, and pelletization was performed.

[0282] In the obtained ethylene·α-olefin rubber reinforced aromatic vinyl resin (B1) (a mixture of component (B1) as rubber-reinforced vinyl graft resin (B) and component (C1) as aromatic vinyl copolymer resin (C)), the content of ethylene·α-olefin rubber polymer was 30% (calculated from polymerization conversion), the acetone insoluble fraction was 47%, the acetone soluble fraction was 53%, the grafting ratio was 55%, the intrinsic viscosity [η] of the acetone soluble fraction was 0.33 dL / g, and the melting point measured in accordance with JIS K7121-1987 was 40°C. In addition, the weight average particle size (volume average particle size) and number average particle size of the ethylene·α-olefin rubber polymer in the solution polymerization system determined by the above-mentioned measurement method 2 (transmission electron microscope photograph resolution treatment) were 0.45 μm and 0.35 μm, respectively.

[0283] <Production Example 2: Production of a mixed product of component (B2) and component (C2)>

[0284] 100 parts of the same ethylene-propylene copolymer as that used in Production Example 1, 20 parts of maleic anhydride-modified polyethylene ("Mitsui High Wax 2203A" manufactured by Mitsui Chemicals, Inc., mass average molecular weight: 2,700, acid value: 30 mg / g) as an acid-modified olefin polymer, and 5 parts of tallow fatty acid potassium (a mixture of potassium oleate, potassium stearate, and potassium palmitate) as an anionic emulsifier were mixed. The mixture was supplied at 4 kg / Hr from the hopper of a twin-screw extruder ("PCM30" manufactured by Ikegai Co., Ltd., L / D=40), and an aqueous solution obtained by mixing 0.5 parts of potassium hydroxide and 2.4 parts of ion-exchanged water was continuously supplied from a supply port provided at the exhaust port of the twin-screw extruder, while heating to 220°C for melt kneading and extrusion. The molten kneaded product was continuously supplied to a cooling device installed at the front end of the twin-screw extruder and cooled to 90°C. Then, the solid discharged from the front end of the twin-screw extruder was put into warm water at 80°C, and was continuously dispersed and diluted to a solid content concentration of about 40%, thereby obtaining an aqueous dispersion of olefin resin. The particle size of the ethylene-α-olefin rubber polymer in the obtained olefin resin was determined by the above-mentioned measurement method 1 (dynamic light scattering method), and the result was a weight average particle size of 0.40 μm (number average particle size: 0.26 μm).

[0285] An aqueous olefin resin dispersion (60 parts in terms of solid content of ethylene-propylene copolymer) was added to a stainless steel polymerization tank equipped with a stirrer, and ion exchange water was added to the aqueous olefin resin dispersion so that the solid content concentration was 30%. 0.006 parts of ferrous sulfate, 0.3 parts of sodium pyrophosphate, 0.35 parts of fructose and 1.0 parts of potassium tallow fatty acid (a mixture of potassium oleate, potassium stearate and potassium palmitate) were added, and the temperature was kept at 80°C. 30 parts of styrene, 10 parts of acrylonitrile and 1.0 parts of cumene hydroperoxide were continuously added thereto over 150 minutes, and the polymerization temperature was kept at 80°C to carry out emulsion polymerization to obtain an aqueous dispersion containing an ethylene-α-olefin rubber-reinforced aromatic vinyl resin. An antioxidant was added to the aqueous dispersion containing a rubber-modified graft polymer, and the solid content was precipitated with sulfuric acid. After dehydration, washing and drying, a powdery ethylene-α-olefin rubber-reinforced aromatic vinyl resin was obtained.

[0286] In the obtained ethylene·α-olefin rubber reinforced aromatic vinyl resin (B2) (a mixture of component (B2) as a rubber reinforced vinyl grafted resin (B) and component (C2) as an aromatic vinyl copolymer resin (C)), the content of ethylene·α-olefin rubber polymer is 60% (calculated by polymerization conversion rate), the acetone insoluble component is 84%, the acetone soluble component is 16%, the grafting rate is 40%, the intrinsic viscosity [η] of the acetone soluble component is 0.37 dL / g, and the melting point measured according to JIS K7121-1987 is 42°C.

[0287] In addition, the measured value of the average particle diameter in the following components (B3) and (B5) is based on the said measurement method 1 (dynamic light scattering method).

[0288] <Production Example 3: Production of a mixed product of component (B3) and component (C3)>

[0289] In a glass flask with an internal volume of 7 liters equipped with a stirrer, 75 parts of ion exchange water, 0.5 parts of potassium rosinate, 0.1 parts of tert-dodecyl mercaptan, 40 parts (solid content) of polybutadiene rubber latex (weight average particle size: 0.40 μm, number average particle size: 0.26 μm, gel content: 85%), 15 parts of styrene and 5 parts of acrylonitrile were placed in a nitrogen stream, and the temperature was raised while stirring. When the internal temperature reached 45°C, a solution prepared by dissolving 0.2 parts of sodium pyrophosphate, 0.01 parts of ferrous sulfate heptahydrate and 0.2 parts of glucose in 20 parts of ion exchange water was added, and further stirred. Then, 0.07 parts of cumene hydroperoxide was added to start polymerization.

[0290] After polymerization for 1 hour, 50 parts of ion exchange water, 0.7 parts of potassium rosinate, 45 parts of styrene, 15 parts of acrylonitrile, 0.05 parts of tert-dodecyl mercaptan and 0.01 parts of cumene hydroperoxide were added continuously for 3 hours. The polymerization was continued for 1 hour, and 0.2 parts of 2,2'-methylene-bis(4-ethyl-6-tert-butylphenol) were added to complete the reaction. The polymerization conversion rate was 98%. From the latex as the reaction product, the resin component was coagulated with an aqueous sulfuric acid solution and washed with water, and then dried to obtain a rubber-reinforced aromatic vinyl resin (B3) (a mixture of component (B3) as a rubber-reinforced vinyl graft resin (B) and component (C3) as an aromatic vinyl copolymer resin (C)).

[0291] The obtained butadiene rubber reinforced aromatic vinyl resin had a polybutadiene rubber content of 40% (measured using thermal decomposition gas chromatography), an acetone-insoluble component of 67%, an acetone-soluble component of 33%, a grafting rate of 68%, an intrinsic viscosity [η] of the acetone-soluble component of 0.45 dL / g, and no melting point measured according to JIS K7121-1987 was observed.

[0292] <Production Example 4: Production of a mixed product of component (B4) and component (D4)>

[0293] The synthesis was carried out in the same manner except that the styrene and acrylonitrile in Production Example 3 were changed to 43 parts of styrene, 14 parts of acrylonitrile and 3 parts of methacrylic acid. The obtained butadiene rubber reinforced aromatic vinyl resin (B4) (a mixture of component (B4) as a rubber-reinforced vinyl grafted resin (B) and component (D4) as an acid-modified vinyl resin (D). The mixture may also contain an aromatic vinyl copolymer resin (C), but in a very small amount. A mixture of component (B4) and component (D4) is prepared.) had a polybutadiene rubber content of 40% (measured using thermal decomposition gas chromatography), an acetone-insoluble component of 52%, an acetone-soluble component of 48%, a grafting ratio of 30%, an intrinsic viscosity [η] of the acetone-soluble component of 0.56 dL / g, and no melting point was observed as measured according to JIS K7121-1987.

[0294] <Production Example 5: Production of a mixed product of component (B5) and component (C5)>

[0295] In a glass flask with an internal volume of 7 liters equipped with a stirrer, 75 parts of ion exchange water, 0.5 parts of potassium rosinate, 0.1 parts of tert-dodecyl mercaptan, 40 parts (solid content) of polybutadiene rubber latex (weight average particle size: 0.10 μm, number average particle size: 0.08 μm, gel content: 85%), 15 parts of styrene and 5 parts of acrylonitrile were placed in a nitrogen stream, and the temperature was raised while stirring. When the internal temperature reached 45°C, a solution prepared by dissolving 0.2 parts of sodium pyrophosphate, 0.01 parts of ferrous sulfate heptahydrate and 0.2 parts of glucose in 20 parts of ion exchange water was added, and further stirred. Then, 0.07 parts of cumene hydroperoxide was added to start polymerization.

[0296] After polymerization for 1 hour, 50 parts of ion exchange water, 0.7 parts of potassium rosinate, 45 parts of styrene, 15 parts of acrylonitrile, 0.05 parts of tert-dodecyl mercaptan and 0.01 parts of cumene hydroperoxide were added continuously for 3 hours. The polymerization was continued for 1 hour, and 0.2 parts of 2,2'-methylene-bis(4-ethyl-6-tert-butylphenol) were added to complete the reaction. The polymerization conversion rate was 98%. From the latex as the reaction product, the resin component was coagulated with an aqueous sulfuric acid solution and washed with water, and then dried to obtain a rubber-reinforced aromatic vinyl resin (B5) (a mixture of component (B5) as a rubber-reinforced vinyl graft resin (B) and component (C5) as an aromatic vinyl copolymer resin (C)).

[0297] The obtained butadiene rubber reinforced aromatic vinyl resin had a polybutadiene rubber content of 40% (measured using thermal decomposition gas chromatography), an acetone-insoluble component of 67%, an acetone-soluble component of 33%, a grafting rate of 68%, an intrinsic viscosity [η] of the acetone-soluble component of 0.45 dL / g, and no melting point measured according to JIS K7121-1987 was observed.

[0298] <Aromatic vinyl resin (C)>

[0299] AS resin "SAN-H" (trade name) manufactured by Techno UMG (intrinsic viscosity [η]: 0.80 dL / g) was used.

[0300] <Production Example 6: Production of Acid-modified Vinyl Resin (D)>

[0301] Into a reactor equipped with a stirrer, 250 parts of water, 3 parts of sodium laurate, 0.2 parts of tert-dodecyl mercaptan, 0.4 parts of sodium formaldehyde sulfoxylate, 0.0025 parts of ferrous sulfate, 0.01 parts of disodium ethylenediaminetetraacetate, and 0.5 parts of cumene hydroperoxide were added to deoxygenate the reactor. Then, 73 parts of α-methylstyrene were added while stirring at 60° C. in a nitrogen stream. After sufficient emulsification, 17 parts of acrylonitrile as a component other than α-methylstyrene was continuously added dropwise over 5 hours to carry out copolymerization, and the polymerization was terminated when the polymerization conversion reached 85.0%.

[0302] Next, 0.5 parts of cumene hydroperoxide, 0.05 parts of tert-dodecyl mercaptan, 0.4 parts of sodium formaldehyde sulfoxylate, 0.0025 parts of ferrous sulfate and 0.01 parts of disodium ethylenediaminetetraacetate were further added to the polymerization solution. Then, 2 parts of styrene, 3 parts of acrylonitrile and 5 parts of methacrylic acid were continuously added dropwise for 0.5 hours while stirring at 60°C in a nitrogen stream to carry out copolymerization. After the addition was completed, the mixture was stirred at 60°C for 1.5 hours to terminate the polymerization. The final polymerization conversion rate was 96.0%. Regarding the amount of residual monomers in the reactor, α-methylstyrene was 1.4%, styrene was 0.2%, acrylonitrile was 1.2%, and methacrylic acid was 1.2% relative to the total amount of monomers to be polymerized. Then, the mixture was coagulated using calcium chloride and recovered using an extruder "DMG40mm" (model name) with a vent manufactured by PLACON Co., Ltd. to obtain an acid-modified vinyl resin (D) having an intrinsic viscosity [η] of 0.31 dL / g.

[0303] <Filling material>

[0304] Glass fiber: Glass fiber "MA FT698" (trade name) manufactured by Owens Corning (fibrous, fiber length 3 mm, fiber diameter 13 μm) was used.

[0305] <Other thermoplastic resins>

[0306] PA6: A polyamide resin "Novamid 1015" (trade name) manufactured by Mitsubishi Engineering-Plastics Corporation (polyamide 6, plant content: 0%, melting point: 225° C.) was used.

[0307] [Examples 1 to 30, Comparative Examples 1 to 9]

[0308] The components listed in Tables 1 to 5 were mixed in the mixing ratios listed in Tables 1 to 5 using a Henschel mixer, melt-kneaded using a twin-screw extruder (TEX44α manufactured by The Japan Steel Works, Ltd., barrel setting temperature 250° C.), and pelletized to obtain a thermoplastic resin composition.

[0309] The obtained thermoplastic resin composition was subjected to the above-mentioned measurements and evaluations. The results are shown in Tables 1 to 5.

[0310] In addition, Tables 1 to 5 also describe the plant content of the produced thermoplastic resin compositions.

[0311] [Table 1]

[0312]

[0313]

[0314] [Table 2]

[0315]

[0316]

[0317] [Table 3]

[0318]

[0319]

[0320] [Table 4]

[0321]

[0322]

[0323] ※ The weight average particle size of the rubber polymer (b) is shown in the parentheses in the column of rubber-reinforced aromatic vinyl resin (B1) to (B5) [Table 5]

[0324]

[0325]

[0326] The following can be seen from Tables 1 to 5.

[0327] Since Examples 1 to 30 are within the range of the requirements of the present invention, they have good moldability, and are excellent in impact resistance, chemical resistance, long-term durability, and squeaking noise suppression.

[0328] On the other hand, since the polyamide (A) was not compounded in Comparative Examples 1 and 2, the long-term durability and the squeaking noise suppression were inferior.

[0329] Since the compounding amount of the polyamide (A) in Comparative Examples 3 and 4 was outside the range of the present invention, any of the impact resistance, chemical resistance, and long-term durability was inferior.

[0330] Since the compounding amount of the rubber-reinforced vinyl resin (B) in Comparative Examples 5 and 6 was outside the range of the present invention, any of the impact resistance, chemical resistance, and squeaking noise suppression was poor.

[0331] Since the compounding amount of the acid-modified vinyl resin (D) in Comparative Examples 7 and 8 was outside the range of the present invention, any of moldability, impact resistance, and squeaking noise suppression was inferior.

[0332] From the comparison between Example 26 and Comparative Example 9, it is understood that even when a filler such as glass fiber is added, excellent impact resistance and long-term durability can be achieved by blending the polyamide (A).

[0333] Examples 27 to 30 are examples of using a rubber-reinforced aromatic vinyl resin (B5) containing a rubber polymer (b) with a small particle size of 0.10 μm by weight as the rubber-reinforced vinyl graft resin (B). Compared with other examples that do not use a rubber-reinforced aromatic vinyl resin (B5) containing such a small particle size of the rubber polymer (b), the Charpy impact strength and the noise risk index are inferior. This tendency is also significantly reflected in Example 27 using a very small amount of the rubber-reinforced aromatic vinyl resin (B5).

[0334] Although the present invention has been described in detail using specific embodiments, it is apparent to those skilled in the art that various modifications can be made within the scope of the invention.

[0335] This application is based on Japanese patent application No. 2022-165619 filed on October 14, 2022, and all contents thereof are incorporated by reference.

[0336] Industrial Applicability

[0337] The thermoplastic resin composition of the present invention can be suitably used as a molding material for molded articles that are excellent in moldability and are required to have impact resistance, chemical resistance, long-term durability, and reduced squeaking.

[0338] Description of Reference Numerals

[0339] 10, 18, 20, 28 parts

[0340] 19 Axis

[0341] 29 Opening

[0342] 30 Protrusion

[0343] 31 Adhesive

[0344] 33 Bolts and nuts

Claims

1. A thermoplastic resin composition comprising a polyamide (A) at least part of which is derived from biomass, a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C) and an acid-modified vinyl resin (D), wherein: In 100 parts by weight of the total of polyamide (A), rubber-reinforced vinyl graft resin (B), aromatic vinyl copolymer resin (C) and acid-modified vinyl resin (D), 20 to 70 parts by weight of polyamide (A), 5 to 45 parts by weight of rubber-reinforced vinyl graft resin (B), 10 to 75 parts by weight of aromatic vinyl copolymer resin (C) and acid-modified vinyl resin (D) and 0.1 to 40 parts by weight of acid-modified vinyl resin (D) are contained.

2. The thermoplastic resin composition according to claim 1, wherein The rubber-reinforced vinyl-based graft resin (B) comprises a rubber polymer (b) portion and a resin (m) portion grafted to the rubber polymer (b) and comprising a structural unit derived from a vinyl-based monomer. The weight average particle size of the rubber polymer (b) is 0.20 to 0.70 μm.

3. The thermoplastic resin composition according to claim 2, wherein The rubber-reinforced vinyl graft resin (B) contains, as the rubber polymer (b), an ethylene / α-olefin rubber polymer (b1) having a melting point of 0 to 100° C. as measured in accordance with JIS K7121-1987.

4. The thermoplastic resin composition according to claim 3, wherein The rubber-reinforced vinyl graft resin (B) is obtained by polymerizing a vinyl monomer including an aromatic vinyl compound in the presence of an ethylene-α-olefin rubber polymer (b1) having a melting point of 0 to 100° C. as measured in accordance with JIS K7121-1987. 5 . A molded article comprising the thermoplastic resin composition according to claim 1 .

Citation Information

Patent Citations

  • Rubber modified nylon composition

    JP1995084549B2

  • Thermoplastic resin composition

    JP2002212383A

  • Automobile interior trimming part with reduced creak noise

    JP2011168186A

  • Powder containing composite rubber-based graft copolymer, coagulation containing composite rubber-based graft copolymer, thermoplastic resin composition and molded article thereof

    JP2016125006A

  • Thermoplastic resin composition and molded article

    JP2019172759A